Effect of Metal‐Support Interactions in Mixed Co/Al Catalysts for Dry Reforming of Methane. Issue 15 (9th July 2019) - Horlyck, Jonathan; Sara, Marina; Lovell, Emma C.; Amal, Rose; Scott, Jason
Abstract: Composite Co/Al oxide materials were prepared via flame spray pyrolysis and examined as catalysts for the dry reforming of methane. The interaction between the metal (Co) and the support (Al‐oxide) was regulated by varying the Co : Al ratio and its influence on catalyst performance studied. The synthesis of materials with a Co content of 30 mol % (Co3 Al7 ) promoted the formation of readily reduced and highly‐dispersed Co particles. This, in combination with a high relative surface basicity, contributed to Co3 Al7 delivering a high and stable activity towards the dry reforming reaction. The formation of bulk Co3 O4 particles, which exhibit weak interactions with the support material, in samples with a Co content of 50 (Co5 Al5 ) and 70 mol % (Co7 Al3 ) caused rapid catalyst deactivation via coking. The findings demonstrate the importance of metal‐support interactions between the Co catalyst and Al‐oxide support for the activity and selectivity in the dry reforming of methane. Highly dispersed Co deposits and high support basicity, induced by an ideal FSP Co : Al synthesis ratio, are key to delivering an active and stable catalyst for the dry reforming of methane. Abstract : Catalyst on fire ! Metal support interactions (MSI) were varied in mixed Co/Al catalysts for the dry reforming of methane. Optimum MSI for the catalyst with 30 mol % of Co resulted in small Co deposits, enhanced Co reducibility and high relative surface basicity. This led to high catalytic activity and stability. Catalyst performance became worse when the MSI was weakened by increasing Co content (>50 mol %).